For the life of the world : theology that makes a difference - Volf, Miroslav; Croasmun, Matthew, 1979- (Grand Rapids.: : Brazos Press, 2019)
"Shows that a recovery of theology is vital to help us evaluate contested questions of value, articulate compelling visions of the good life, and answer the fundamental question of what makes a life worth living"--
Introduction: why theology matters-to us -- The quest for the flourishing life -- The crisis of theology -- The renewal -- The challenge of universality -- Lives of theologians with Justin Crisp -- A vision of flourishing life.
Includes bibliographical references and index.
Keywords: Theology, Practical; Christian life